2006
DOI: 10.1007/s10508-006-9130-7
|View full text |Cite
|
Sign up to set email alerts
|

Biological, Familial, and Peer Influences on Dating in Early Adolescence

Abstract: The current study examined the joint contributions of pubertal maturation, parental monitoring, involvement in older peer groups, peer dating, and peer delinquency on dating in a sample of early adolescent boys and girls. The sample consisted of 784 adolescents (394 boys, 390 girls) enrolled in grades 5, 6, and 7 who were followed for one year. In addition to measures of pubertal maturation and parental monitoring, adolescents and their peer group members completed indices of dating and delinquency. Average da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 47 publications
5
60
1
1
Order By: Relevance
“…Thus, researchers have found that adolescents from families who have experienced marital separation and/or parental remarriage tend to experience less closeness and family support as a result of decreased parental monitoring (typically from the spouse with custody), increased conflict between parents and other related problems. Consequently, as a result of increased instability in the family environment (Cavanagh, Crissey, & Raley, 2008;Ivanova, Mills, & Veenstra, 2011) and less parental supervision (Friedlander, Connolly, Pepler, & Craig, 2007), the children may more easily and sooner engage in romantic and sexual relationships (Cavanagh et al, 2008) and manifest internalizing and externalizing behavioral problems (Hetherington, 2003;Vanassche, Sodermans, Matthijs, & Swicegood, 2014). In addition, the romantic relationships of adolescents may be a way to escape the unstable family environment and provide comfort and warmth (Cavanagh et al, 2008;Ivanova et al, 2011).…”
mentioning
confidence: 99%
“…Thus, researchers have found that adolescents from families who have experienced marital separation and/or parental remarriage tend to experience less closeness and family support as a result of decreased parental monitoring (typically from the spouse with custody), increased conflict between parents and other related problems. Consequently, as a result of increased instability in the family environment (Cavanagh, Crissey, & Raley, 2008;Ivanova, Mills, & Veenstra, 2011) and less parental supervision (Friedlander, Connolly, Pepler, & Craig, 2007), the children may more easily and sooner engage in romantic and sexual relationships (Cavanagh et al, 2008) and manifest internalizing and externalizing behavioral problems (Hetherington, 2003;Vanassche, Sodermans, Matthijs, & Swicegood, 2014). In addition, the romantic relationships of adolescents may be a way to escape the unstable family environment and provide comfort and warmth (Cavanagh et al, 2008;Ivanova et al, 2011).…”
mentioning
confidence: 99%
“…Indeed, research showed that, for adolescent girls, other-sex friendships are associated with problem behavior whereas it 22 is not the case for boys (e.g., Arndorfer & Stormshak, 2008;Mrug et al, 2011). Moreover, parents seem to monitor the activities of their daughters more closely than those of their sons (e.g., Crouter et al, 2005;Friedlander et al, 2007) and may pay more attention to the gender of their daughters' peers.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, levels of monitoring knowledge are greater for female than for male children (Crouter et al, 2005;Friedlander et al, 2007;Pettit et al, 2001;Smetana & Daddis, 2002;Svensson, 2003;Waizenhofer et al, 2004). Regarding friends, researchers usually focus on their behavioral orientation (e.g., whether they engage in delinquency or substance use), but have never specifically considered their gender.…”
Section: Parenting Adolescent Gender and Gender Of Friendsmentioning
confidence: 99%
“…Following divorce, parents have less energy and less power to monitor their child's behavior, and this can be linked to an increased likelihood of dating (Friedlander et al 2007). On the other hand, continuous maternal sensitivity to their needs (Roisman et al 2009) can protect adolescents from risky romantic behavior and promote age-appropriate romantic relationships.…”
Section: Parental Divorce and Adolescent Romantic Relationshipsmentioning
confidence: 99%